The Effect of Educational Game-Based Learning on Cognitive Abilities in Early Childhood - Dara Gebrina Rezieka; Maiyida Safita; Nurma Nurma; Mursyidah Mursyidah; Mauliady Satria (Suluah Pasaman, 2026)
Despite increasing interest in game-based learning, empirical evidence on its impact in Indonesian early childhood education (ECE) remains scarce, with prior studies lacking validated instruments and inferential analyses. This study employed a sequential exploratory mixed-methods design to examine the effect of educational game-based learning on six cognitive indicators—concept identification, classification, memory recall, problem-solving, logical reasoning, and symbolic representation—among children aged 5–6 years (n = 40) at Sabbihisma 2 Kindergarten, Padang. Qualitative data were collected through structured observation, semi-structured interviews, and documentation. Quantitative data were obtained using a 10-item observational rubric (4-point Likert scale; κ = .82) aligned with Indonesia’s national ECE developmental standard (STPPA). Mean cognitive scores increased from M = 36.8 (SD = 1.9) pre-intervention to M = 38.2 (SD = 1.4) post-intervention. A paired-samples t-test confirmed the improvement was statistically significant, t(39) = 3.21, p < .01. The proportion of children achieving the highest developmental category (BSB) rose from 75% to 90%. Qualitative findings corroborated enhanced engagement, logical reasoning, and problem-solving behaviors. Educational game-based learning significantly improved cognitive outcomes in ECE settings. Findings support institutionalizing structured game programs and investing in teacher professional development for technology-integrated pedagogy.